The pattern of substance use disorder in the United Arab Emirates in 2015: results of a National Rehabilitation Centre cohort study. Issue 1 (December 2016) - Alblooshi, Hiba; Hulse, Gary K.; El Kashef, Ahmed; Al Hashmi, Hanan; Shawky, Mansour; Al Ghaferi, Hamad; Al Safar, Habiba; Tay, Guan
Abstract Background Substance use disorder (SUD) is a global problem with no boundaries, which also afflicts individuals from countries of the Arabian Peninsula. Data from this region is limited. In an effort to develop targeted prevention and intervention initiatives in the United Arab Emirates (UAE), it was necessary to identify the nature of substance use by describing the characteristics of those using different substances. Consequently, this study in the UAE was conceived to describe the pattern of SUD in a first-ever cohort that was systematically recruited from the country's National Rehabilitation Centre (NRC) in Abu Dhabi. Methods Two hundred and fifty male patients were recruited from the NRC. Information on substance use was collected using a questionnaire that was completed at an interview with patients who consented to participate. The questionnaire was based on information that the study was designed to capture. It was reviewed by members of institutional ethics committees and approved prior to use. Two hundred and fifty male subjects from the Emirates Family Registry (EFR) were used as a comparison group. Results In the cohort studied, SUD correlated with smoking and marital status. Poly-substance users formed the majority of the cohort (84.4 %) with various combinations of substances identified across different age groups. Opioid and alcohol were the most common substances used. The use of pharmaceutical opioids, primarily Tramadol (67.2 % of opioid users), was higher among the youngest age group studied (<30 years old), while older opioid users (≥30 years old) commonly used illicit opioids (Heroin). The use of prescribed medication for non-medical use also included Pregabalin (mean of 8.3 capsules ± 0.5 per day), Procyclidin (6.1 tablets + 0.6 per day) and Carisoprodol (4.2 tablets ± 0.4 per day) and was again highest in the age group below 30 years. Conclusion This 2015 study highlights the importance of examining the pattern of poly-substance use in a population in order to develop targeted prevention programs to arrest the prevailing trends. It has drawn attention to the rise in use of prescription medication in the UAE, in particular among younger patients (<30 years), and continuing use of illicit opioid amongst males above 30 years. Specific prevention and intervention strategies, targeting differences between these distinct demographic profiles will capture a large subset of sufferers.